PFO closure with only fluoroscopic guidance: 7 years real‐world single centre experience. Issue 1 (19th March 2015) - Mangieri, Antonio; Godino, Cosmo; Montorfano, Matteo; Arioli, Francesco; Rosa, Isabella; Ajello, Silvia; Piraino, Daniela; Monello, Alberto; Pavon, Anna Giulia; Viani, Giacomo; Magni, Valeria; Cappelletti, Alberto; et al.
<x xml:space="preserve">Abstract</x> Aims To evaluate the safety and the efficacy of fluoroscopy‐guided only (Fluo‐G) and of echocardiography‐guided (Echo‐G; trans‐esophageal echocardiography—TEE—or intracardiac echocardiography‐ICE) percutaneous closure of patent foramen ovale (PFO). Methods and Results Single center retrospective registry enrolling 368 consecutive patients (mean age 50.5 years) who underwent PFO closure between June 2004 and December 2011. Most patients had prior cryptogenic stroke (n = 126; 34.2%), TIA (n = 218; 51.1%); some of these had recurrent neurological events [multiple strokes n = 28 (7.8%); multiple TIAs n = 72 (18.6%)]. All the patients underwent a preprocedure TEE. PFO closure was performed with Echo‐G in 187 patients (50.8%) (TEE n = 69, 36.8% and ICE n = 124, 66.3%). In Fluo‐G cases, PFO with atrial septal aneurysm (ASA) was significantly less present (P < 0.005) and smaller devices (<25 mm) were implanted more frequently (P < 0.001). Both fluoroscopy and total procedural time were lower in the Fluo‐G group (P < 0.0001). No differences were found in terms of successful device deployment (98.3% Fluo‐G vs. 98.3% Echo‐G) and RtL‐shunt at follow‐up (11.7% Fluo‐G vs. 7.6% Echo‐G). The rate of conversion from Fluoro‐G to Echo‐G procedure was 4.4% (n = 8). At a median follow‐up of 4 years, freedom from recurrent embolic events rate was similar between the two groups (Echo‐G 94.5 vs. Fluo‐G 95.7%). Conclusions In our experience Fluoro‐G PFO closure was performed mainly in cases of simple anatomy, with similar results in terms of safety and efficacy compared to Echo‐G cases. Both fluoroscopy and total procedural times were lower in the Fluo‐G cases. © 2015 Wiley Periodicals, Inc.